Маша и медведь: [сказка] / [худ. В. А. Жигарев] - Жигарев В.А. (ФЛАМИНГО, 2010)
Экземпляры: ф.15,9,20,19,24 (01.07.2011) / Инвентарный номер: zzzzz / Цена: 8.00 / Авт.знак: М 38 / ГРНТИ: 17.82 / ББК: 82.3(2Рос=Рус)-6